The Decrease of Legislative Functions of The People's Representative Council of The Republic of Indonesia in The Reform Era - M.Nur Rasyid; Sri Maulina; Manfarisyah Manfarisyah (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The indicator of the running of the legislative body's role is the production of pro-people legal products. However, in the reform era, the role of the People's Representative Council of the Republic of Indonesia has decreased as a legislative body. The decline in the role of the People's Representative Council of the Republic of Indonesia in the reform era was influenced by several factors. It is necessary to examine the factors causeby the weak role of the People's Representative Council of the Republic of Indonesia and also the implications of the Constitutional Court Decision on the Job Creation Act. This study aims to explain the causes of the decline in such a role and to explain the role of the People's Representative Council of the Republic of Indonesia in the formation of the law. This type of research is normative juridical. The results of the study indicate that there has been a weakening of the role of the People's Representative Council of the Republic of Indonesia in the reform era caused by several factors such as the weakening of the political parties' power, the large number of political parties in coalition with the government, as well as the large intervention of the economic elite in political parties and the government, which resulted in a controversy over the formation of Job Creation Act caused by the non-applicability of the principles of the formation of good legislation by legislators at the time of making the law.